Need of Assessment of the Quality of Life in Patients after Coronary Artery Bypass Grafting - Jyothi (Indian Journal of Nursing Sciences, 2024)
Among the non-communicable disease burden which is on rise globally; cardiovascular diseases attribute to the major cause of mortality and morbidity worldwide. The management of coronary artery disease may be tackled by non-invasive or invasive techniques such as coronary artery bypass grafting (CABG). In spite of advances in operative techniques of CABG; the care in the rehabilitation phase holds vital importance. Quality of life (QoL) after CABG needs to promote by equal efforts of the health-care team along with initiatives of the patients when he returns home from the hospital setting. Nurses’ participation in the secondary prevention of complications in the post-CABG period definitely enhances the QoL of the patients.